2011
DOI: 10.5209/rev_sjop.2011.v14.n1.23
|View full text |Cite
|
Sign up to set email alerts
|

Personal and Situational Variables, and Career Concerns: Predicting Career Adaptability in Young Adults

Abstract: This study examined relationships among career adaptability and career concerns, social support and goal orientation. We surveyed 304 university students using measures of career concerns, adaptability (career planning, career exploration, self-exploration, decision-making, self-regulation), goal-orientation (learning, performance-prove, performance-avoid) and social support (family, friends, significant others). Multiple regression analysis revealed career concerns, learning and performance-prove goal orienta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 54 publications
5
26
0
3
Order By: Relevance
“…Career exploration has been found to be associated positively with mastery and performance approach in children and young adults, although not consistently (Creed et al, 2009;Creed, Buys, Tilbury, & Crawford, 2013;Yousefi, Abedi, Baghban, Eatemadi, & Abedi, 2011), and stronger correlations have been found for mastery approach than for performance approach (Creed et al, 2009). Career exploration has been found to be associated positively with mastery and performance approach in children and young adults, although not consistently (Creed et al, 2009;Creed, Buys, Tilbury, & Crawford, 2013;Yousefi, Abedi, Baghban, Eatemadi, & Abedi, 2011), and stronger correlations have been found for mastery approach than for performance approach (Creed et al, 2009).…”
Section: Goal Orientation and Vocational Identitymentioning
confidence: 95%
See 1 more Smart Citation
“…Career exploration has been found to be associated positively with mastery and performance approach in children and young adults, although not consistently (Creed et al, 2009;Creed, Buys, Tilbury, & Crawford, 2013;Yousefi, Abedi, Baghban, Eatemadi, & Abedi, 2011), and stronger correlations have been found for mastery approach than for performance approach (Creed et al, 2009). Career exploration has been found to be associated positively with mastery and performance approach in children and young adults, although not consistently (Creed et al, 2009;Creed, Buys, Tilbury, & Crawford, 2013;Yousefi, Abedi, Baghban, Eatemadi, & Abedi, 2011), and stronger correlations have been found for mastery approach than for performance approach (Creed et al, 2009).…”
Section: Goal Orientation and Vocational Identitymentioning
confidence: 95%
“…Not all of these relationships have been tested in the career domain; thus, our propositions here are somewhat exploratory. Career exploration has been found to be associated positively with mastery and performance approach in children and young adults, although not consistently (Creed et al, 2009;Creed, Buys, Tilbury, & Crawford, 2013;Yousefi, Abedi, Baghban, Eatemadi, & Abedi, 2011), and stronger correlations have been found for mastery approach than for performance approach (Creed et al, 2009). For performance avoidance, studies have found exploration to be both unrelated (Creed et al, 2013;Yousefi et al, 2011) and negatively related (Creed et al, 2009).…”
Section: Goal Orientation and Vocational Identitymentioning
confidence: 95%
“…However, each predictor contributes uniquely to the prediction of career adaptability components. Overall career adaptability is predicted by cognitive ability, the Big Five personality traits (Rudolph et al, 2017), future temporal focus (Zacher, 2014), a proactive personality (Guan et al, 2017;Jiang, 2017), positive emotional disposition (Hirschi, 2009), motivation (Pouyaud, Vignoli, Dosnon, & Lallemand, 2012), explicit and implicit self-esteem (Hui, Yuen, & Chen, 2018;Negru-Subtirica & Pop, 2016;Cai et al, 2015;Rusu, Măirean, Hojbotă, Gherasima, & Gavriloaiei, 2015), core self-evaluation (Guan et al, 2017;Neureiter & Traut-Mattausch, 2017;Zacher, 2014), career self-efficacy, personal goal orientation, and career future concern (Ebenehi, Rashid, & Bakar, 2016;Wang & Fu, 2015), and learning goal orientation (Guan et al, 2017;Yousefi, Abedi, Baghban, Eatemadi, & Abedi, 2011).…”
Section: Empirical Findings About Career Adaptabilitymentioning
confidence: 99%
“…Generally it can be explained that the student of faculty of education student have medium career adaptability specially in career concern [4] and longterm orientation and a feeling of optimism as professional workers are also in the medium category. Though low concern can lead to pessimism career will be successful in the future.…”
Section: Advances In Social Science Education and Humanities Researcmentioning
confidence: 99%
“…Career concern regarding to awareness of one's career his future as a professional [4]. Career concern also associated with long-term orientation and a feeling of optimism as workers.…”
Section: Introductionmentioning
confidence: 99%